Współczesne teorie wymiany międzynarodowej. Światowy handel po kryzysie 2008 r. - Kundera, Jarosław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The theory of international economic exchange are in constant development under the influence of the evolution of the world economy, especially after the crisis of 2008. Due to the complex nature of contemporary international exchange describing them theories must consist of having several theoretical concept, because the division of labour in the global economy develops through the exchange of both „products of Ricardo”, products of „Heckscher-Ohlin” and „advanced technology products”. The crisis of 2008, brings however a qualitative change in international space thanks to an increase in demand for products technologically advanced, diversity, by decreasing the importance of exchange of raw materials and fuels. Increasing position in the trade, so called new industrial countries and the decreasing position of developed countries indicates the importance factor of competitiveness, human capital, increasing technological gap theory rank diffusion, life of the product as best in translating contemporary changes in the international division of labour. Relocation of the world production was often in the context of TNCs, which are producing products in countries with lower costs on the basis of an intra industry trade. Changes in the international division of labour in the period of economic crisis apply not only to the structure of the turnover, but also the geography of the export and import in connection with the growing importance of China and new industrial countries in the global economy. Central and Eastern Europe countries have improved slightly their position in the world exports, while the visible is the decline in its value in Russia, oil countries like Saudi Arabia, which is associated with a reduction in oil prices.
Keywords: neo-technological theories; the international division of labor; globalization; intra-industry trade; neo-factories theories; trade in services in the world economy; international enterprise; trade technological advanced goods